Las técnicas del teatro del oprimido como estrategia psicoeducativa para prevenir la violencia escolar en los adolescentes de octavo año paralelo B, de la unidad educativa Dr. Manuel Cabrera Lozano, 2018-2019 - Oviedo Severino, Meiri Rosa (2020)
School violence is a social problem that affects the physical and emotional integrity of adolescents. That is why the research called: THE TECHNIQUES OF THE THEATER OF THE OPPRESSED AS A PSYCHOEDUCATIONAL STRATEGY TO PREVENT SCHOOL VIOLENCE IN ADOLESCENTS OF THE EIGHTH PARALLEL YEAR B, OF THE EDUCATIONAL UNIT Dr. MANUEL CABRERA LOZANO, 2018-2019. Its general objective was to implement a psychoeducational strategy based on the techniques of the theater of the oppressed to prevent school violence in adolescents of the eighth parallel year B, of the educational unit Dr. Manuel Cabrera Lozano, 2018-2019. The study was descriptive, cross-sectional and its quasi-experimental design, the methods used in the process the research was scientific, analytical, deductive, inductive and synthetic, as an instrument used for a general aggressiveness scale that was applied to a sample made up of 23 students, aged 12 to 15 years. The results achieved in the pre-test show a high level of verbal aggressiveness 17.39%, as well as psychological aggressiveness 4.35%; and in physical aggressiveness, 70% indicate an average index. After the application of the proposal through the post-test, it was evidenced that said levels were notably reduced in those with a low level of 69.57%, and 65.22% for verbal, psychological, and physical aggressiveness, 39,13% is found in a medium index. It is concluded that there was a high manifestation of a verbal and psychological type and a medium percentage in physical aggressiveness among students. After the execution of the psychoeducational strategy in the investigated, it was possible to reduce the level of school violence, both physical, verbal and psychological. The effectiveness of the activities carried out was 94.6%, the application of the proposal based on the techniques of the theater of the oppressed is validated since it allowed to favor their personal and social development, in 5 addition to promoting spaces for reflection analysis for the prevention of school violence.